Genetic diversity and breeding value of synthetic hexaploid wheat introduced into the VIR collection - A. G. Khakimova; N. K. Gubareva; V. А. Koshkin; O. P. Mitrofanova (Вавиловский журнал генетики и селекции)
For the  successful  development of wheat  breeding in Russia, a genetically  diverse  and  well-characterized starting material, mainly stored  at the VIR collection, is needed. To replenish  the collection, 36 lines (accessions) of synthetic hexaploid  wheat  (SHWs) developed at CIMMYT by crossing Triticum durum with Aegilops tauschii were studied.  Our research  was aimed at studying  the SHWs using a complex of morphological and economically  valuable traits in the environments of European Russia’s northwestern part (E30°, N59°), evaluating the reaction  of the SHWs to a photoperiod  and determining their genetic heterogeneity and similarities by gliadins as biochemical  markers. The results showed that the variability of different traits for SHWs fits into the framework of the genus  Triticum, and so SHWs can be classified as poorly domesticated forms. Their distinctive feature, valuable for wheat  breeding, is a large weight  of a thousand grains (up to 60.6 g). This trait was characterized by a low degree of variability and a low correlation  with other  traits. The reaction  of wheat  plants to the length  of the day is crucial for their transition  from vegetative to reproductive development. The SHWs studied differed from common wheat and one another by responses to the short day and by the length  of the ‘emergence-heading’ phase  if they grew under  the conditions of a long day. The delay in the development of plants with a short photoperiod ranged from 5.4 to 53.8 days. On a long day, the duration of the ‘emergence-heading’ phase  varied from 39.5 to 53.9 days. A possible genetic basis for the differences  identified is discussed.  To assess the diversity of SHWs, we also used  gliadin proteins as informative  biochemical  markers. It was revealed  that 21 SHWs were homogeneous, and the rest, heterogeneous. Forty-four different biotypes were found for the SHWs studied,  from which 36 were unique.  Relationships between biotypes have been  demonstrated using cluster analysis. It should be noted that 13 SHWs were unstable. In each of them, some plants differed from the others  in terms of a complex of morphological characters, reaction to a photoperiod, and gliadin patterns. It is possible that the instability of accessions  is the result of genome rearrangement in SHWs. SHW accessions  and the forms isolated from them are considered as sources of new genetic variability to improve common wheat.